Prolonged exposure to a public health event: the mediating role of resilience between social support and post-traumatic growth among frontline nurses - Dejian Zeng; Yan Li; Caixia Yang; Dan Tang; Yanzhi Yi; Yanjun He; Mingyan Yang (BMC, 2024)
Abstract Background In the early days of December 2022, the Chinese government ended its restrictive quarantine measures (e.g. nationwide lockdown) against COVID-19, which started in December 2019. Three years of prolonged exposure to the COVID-19 pandemic and restrictive quarantine policy had a notable impact on the mental health of frontline nurses. Traumatic events can have negative effects on people as well as positive ones, such as post-traumatic growth (PTG). Studies have revealed that frontline nurses' self-perceived quality of life had not changed significantly when the pandemic's effects lessened. The Chinese model of fighting the pandemic provided a valuable opportunity for studying the effects of prolonged exposure traumatic events on PTG in individuals. Objective This cross-sectional study attempted to investigate PTG and its relationship with social support and resilience among frontline nurses during COVID-19 pandemic. Methods A sample of 378 frontline nurses from tertiary hospitals in China participated in this study. The study took place two weeks after the government announced the end of the quarantine policy in December 2022 in China. Participants' PTG, resilience and social support were assessed using the Post-traumatic Growth Inventory, Social Support Rate Scale and 14-Item Resilience Scale, respectively. PROCESS Procedure Model 4 was employed to examine the mediating role of resilience between social support and PTG. Results The results of mediating effect analysis showed that social support could significantly predict resilience (a = 0.752, SE = 0.079, P < 0.001). Social support could significantly predict PTG (c' = 0.366, SE = 0.103, P < 0.001), and resilience could also significantly predict PTG (b = 0.226, SE = 0.060, P < 0.001). Bootstrap test identified a significant mediating effect of resilience between social support and PTG (ab = 0.170, BootSE = 0.077, 95% CI [0.031, 0.330]). The mediating effect contributed 31.72% of the total effect ([a×b]/c=[0.752 × 0.226]/0.536 = 0.3172), indicating a partial mediating role of resilience between social support and PTG. Conclusion Resilience partially mediated the relationship between social support and PTG among frontline nurses during COVID-19 pandemic. Improving social support and resilience might be effective intervention strategies for promoting PTG among frontline nurses during traumatic events.